1980
DOI: 10.1002/jss.400140102
|View full text |Cite
|
Sign up to set email alerts
|

Divalent cation dependent ATPase activities of red blood cell membranes: Influence of the oxidation of membrane thiol groups close to each other

Abstract: An Mg2+-dependent low ATPase activity can be detected in erythrocyte "white membranes," in addition to that of the well known (Ca2+ + Mg2+)-ATPase. The thiol oxidizing agent diamide affects both activities. The oxidation of neighboring thiols seems to leave the mechanism of the (Ca2+ + Mg2+)-ATPase amplification system evoked by Ca2+ largely unaffected. The perturbation caused by diamide in the membranes seems to affect primarily a step of the ATP hydrolysis mechanism that is common to both ATPase activities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
1995
1995

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…In red blood cells, diamide is known to oxidize glutathione rapidly to GSSG (Kosower, Kosower & Wertheim, 1969) which, in turn, alters the ratio of NADP: NADPH (Elkow, Moldeus & Orrenius, 1984). Oxidation of sulfhydryl groups by diamide has been shown to modulate Ca2+-Mg2+-ATPase activity (Scutari, Ballestrin & Covaz, 1980) and Ca2+ permeability (Branca, Scutari & Siliprandi, 1978). More recently, it has also been shown that the oxidation of glutathione can determine the redox status of cysteine Presented at the Oxford Meeting of the Society in July 1995. residues in the N-terminal of the fl-subunit of K+ channels and, thus, may influence channel gating (Ruppersburg, Stocker, Pongs, Heinemann, Frank & Koenen, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…In red blood cells, diamide is known to oxidize glutathione rapidly to GSSG (Kosower, Kosower & Wertheim, 1969) which, in turn, alters the ratio of NADP: NADPH (Elkow, Moldeus & Orrenius, 1984). Oxidation of sulfhydryl groups by diamide has been shown to modulate Ca2+-Mg2+-ATPase activity (Scutari, Ballestrin & Covaz, 1980) and Ca2+ permeability (Branca, Scutari & Siliprandi, 1978). More recently, it has also been shown that the oxidation of glutathione can determine the redox status of cysteine Presented at the Oxford Meeting of the Society in July 1995. residues in the N-terminal of the fl-subunit of K+ channels and, thus, may influence channel gating (Ruppersburg, Stocker, Pongs, Heinemann, Frank & Koenen, 1991).…”
Section: Introductionmentioning
confidence: 99%